Distribution and Characterization of Diseases of Dragon Fruit (Hylocereus Spp.) in Peninsular Malaysia - Masyahit, Masanto (2010)
Field surveys were conducted from December 2007 to August 2008 at 43 dragon fruit-orchards in Peninsular Malaysia with 50 posts of sampled plants per location. The results revealed that among recorded diseases, anthracnose, brown spot and necrotic spot were encountered in almost all sampled states with the range of frequency around 50 to 100%; whereas fruit brown rot was only found in Negeri Sembilan with frequency of 33.33%. Meanwhile, other diseases such as fruit fungal soft rot, stem end rot and bacterial soft rot occurred in 2, 5 and 6 surveyed states, respectively. Statistical analysis showed that the occurrence of anthracnose and necrotic spot diseases were maximum in Malacca with incidence and severity level around 58.00%; 21.20% and 72.00%; 30.00%, respectively. Meanwhile, the maximum occurrences of bacterial soft rot, brown spot and stem end rot were documented in Johore, Negeri Sembilan and Kelantan with incidence and severity levels of about 17.33%; 4.53%, 94.00%; 25.87%, and 14.00%; 4.20%, respectively. These diseases have strong relationships of incidence and severity with the range of R2 value around 0.8995 to 0.9978. Pearson correlation analysis resulted in the incidence of anthracnose which was significantly correlated with necrotic spot (r value of 0.852 at 0.05 level); whereas bacterial soft rot and brown spot were significantly interrelated with each other at the 0.01 level with r value of 0.515. Similarly, the Pearson coefficient correlation also revealed that bacterial soft rot was negatively correlated with temperature (r value of -0.478 at 0.01 level). The positive correlations were shown by bacterial soft rot and brown spot against altitude with r value of 0.508 and 0.523, respectively at 0.01 level. These diseases were categorized according to the characteristics of symptoms found on diseased plants and group of pathogenic agents. Although a number of bacteria and fungi species could be isolated and identified correspondingly based on their responses to biochemical sources within BiOLOG® Microplate as well as their cultural and morphological characteristics, the pathogenicity test showed that only some (e.g. Enterobacter cloacae, Bipolaris sp., Botryosphaeria sp., Colletotrichum gloeosporioides, and Monilinia sp.) positively resulted in similar symptoms with diseased plants in the field. In the mean time, the presence of viral infection was successfully detected on young stems with necrotic small mottle or spot symptoms.